A Four-Layers Hamburger-Structure PVDF-HFP/Al2O3/PE/PVDF-HFP Composite Separator for Pouch Lithium-Ion Batteries with Enhanced Safety and Reliability. Issue 9 (27th March 2020) - Wang, Zheng; Pang, Peipei; Ma, Zhen; Chen, Hongyu; Nan, Junmin
Abstract : A unique composite separator with four-layers hamburger-structure is prepared and demonstrated to be promising application in lithium-ion batteries (LIBs) with enhanced safety and reliability. Using polyolefin (PE) as substrate, Al2 O3 as heat resistance layer, and 2 layers of polyvinylidene difluoride hexafluoropropylene (PVDF-HFP) on the upper and lower, this PVDF-HFP/Al2 O3 /PE/PVDF-HFP (PH/Al/PE/PH) separator is constructed through a gravure printing and phase transfer process. Compared with PE substrate coating with the mixture of Al2 O3 and PVDF-HFP (PH-Al/PE) separator, the as-prepared separator can further enhance the safety performance of LIBs. In external short and nail tests, the maximum temperatures of LIBs with PH/Al/PE/PH separators (100 °C and 103 °C) are lower than LIBs with PH-Al/PE separators (132 °C and 115 °C). And after hot-box test, the voltage of former (4.13 V) is more stable than later (3.78 V). Meanwhile, compared with PE substrate coated by Al2 O3 (Al/PE), the cycle performance of LIBs with PH/Al/PE/PH separator is significantly improved, and the deformation of LIBs is effectively controlled. Furthermore, the mechanism for the enhancement of safety and reliability of LIBs is elucidated. The results indicate that this separator exhibits promising prospects in the application of LIBs with enhanced safety and reliability.